The study of the potentiation of anticholinergic side effects of tricyclic antidepressives by female sex steroids - Kok, Eric Charl (Rhodes University, Faculty of Pharmacy, Pharmacy, 1981)
It has been recorded that women respond to tricyclic antidepressives with a greater incidence of anticholinergic side effects than men do, particularly women taking an exogenous source of oestrogen. The aim of this study was to investigate the influence that ethinyl oestradiol and Premarin© had on the metabolism of a number of tricyclic antidepressives, and also the influence they had on the binding ability of microsomes to imipramine. Rat hepatocyctes and microsomes were used. Detection techniques used were High Pressure Liquid Chromatography and Spectrophotometry respectively. In addition to these studies, a study of the anticholinergic activity of Nomifensine, tricyclic antidepressives and their derivatives was performed on a rat jujenum. Results conclusively showed that ethinyl oestradiol had a marked influence on the metabolism of the tricyclic antidepressives studied. Premarin© had Iittle, if any influence. However, both ethinyl oestradiol and Premarin© affected the binding of microsomes to imipramine, but ethinyl oestradiol had the greater effect. The parent compound in each case exhibited a higher pAZ value. Results indicate that a possible explanation for the increased anticholinergic side effect is due to an inhibition of the metabolism of the tricyclic antidepressives by oestrogen.
Keywords: Antidepressants; Steroid hormones